The Effectiveness of Public Communications of Medan Petisah Government in Preventing of COVID-19 Virus in Medan - AS, Fadlansyah; Abdurrahman, Abdurrahman; Mailin, Mailin (Budapest International Research and Critics University, 2021)
This study aims to discuss about e Effectiveness of Public Communications of Medan Petisah Government in Preventing of COVID-19 Virus in Medan. This research is qualitative. The basis for the effectiveness of public communication that the researcher proposes is to put more emphasis on public trust to take advantage of cooperation and maintain behavior, which is supported by transparency and community involvement so that mutual understanding is achieved, feels mutual joy, can influence attitudes towards health protocols, maintain relationships with protocols. Health and modeling better behavior in preventing COVID-19. Responding to a pandemic is about public communication, social psychology, and health studies, as well as on epidemiology and virology. Therefore, effective public communication during the COVID-19 period requires a cross-disciplinary perspective that is truly evidence-based and reflects the values of a democratic society, so that the prevention of COVID-19 in Medan City can be realized carefully.